2017
DOI: 10.1007/s13205-017-0860-0
|View full text |Cite
|
Sign up to set email alerts
|

Maize seed endophytic bacteria: dominance of antagonistic, lytic enzyme-producing Bacillus spp.

Abstract: Beneficial aspects of endophytic microorganisms have motivated researchers to explore plant endophytic world. The present study was aimed to isolate and characterize the seed-borne endophytic bacteria from diverse maize genotypes. Eighty maize seed endophytic bacteria (MSEB), isolated from 30 maize genotypes, were characterized using polyphasic approach. The dendrograms and phylogenetic tree generated on the basis of ARDRA analysis and metabolic profiling of endophytic bacteria revealed genotypic and biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 46 publications
(14 reference statements)
3
38
0
1
Order By: Relevance
“…Based on temperature tolerance test, majority of the identified endophytic bacterial species such as Pseudomonas stutzeri, Pantoea dispersa, Enterobacter cowanii, Pseudomonas putida biotype B, Serratia ficaria, Pantoae agglomerans and Rhizobium radiobacte were grow well at temperature 37°C, and only butanolivorans was grow well at a temperature up to 60°C. This finding is correlated with the work of Shrey [29]; he reported that maize seed endophytic bacteria exhibited tolerance to salinity (10%), and temperature up to 60°C. Thus, plant growth promoting traits of the endophytic bacterial species identified from tef seed is very important in climate change scenario with projections of increased intensities of a biotic stresses condition in near future posing problem to agricultural production and productivity.…”
Section: Discussionsupporting
confidence: 87%
“…Based on temperature tolerance test, majority of the identified endophytic bacterial species such as Pseudomonas stutzeri, Pantoea dispersa, Enterobacter cowanii, Pseudomonas putida biotype B, Serratia ficaria, Pantoae agglomerans and Rhizobium radiobacte were grow well at temperature 37°C, and only butanolivorans was grow well at a temperature up to 60°C. This finding is correlated with the work of Shrey [29]; he reported that maize seed endophytic bacteria exhibited tolerance to salinity (10%), and temperature up to 60°C. Thus, plant growth promoting traits of the endophytic bacterial species identified from tef seed is very important in climate change scenario with projections of increased intensities of a biotic stresses condition in near future posing problem to agricultural production and productivity.…”
Section: Discussionsupporting
confidence: 87%
“…Several Bacillus species are remarkably important owing to their use in antibiotic construction and ability to induce production of anti-inflammatory cytokine in vitro (57)(58)(59). The use of Bacillus species to produce a wide range of metabolites having antimicrobial prospective is extensive in the medical and pharmaceutical industries; they can assist plant growth in adverse conditions and also capable of controlling many infections in humans, animals, and plants after applied as an organic control mediator (60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…The leaves of L. lucidum Ait were collected from Shandong University of Traditional Chinese Medicine, China in June 2017. Isolation of the endophytes was carried out according to previous methods with minor changes [ 39 ]. Leaves were cut into 1 × 1 cm 2 squares under aseptic conditions.…”
Section: Methodsmentioning
confidence: 99%